Comparative Genomics of the Campylobacter lari Group. (8th November 2014) - Miller, William G.; Yee, Emma; Chapman, Mary H.; Smith, Timothy P.L.; Bono, James L.; Huynh, Steven; Parker, Craig T.; Vandamme, Peter; Luong, Khai; Korlach, Jonas
Abstract: The Campylobacter lari group is a phylogenetic clade within the epsilon subdivision of the Proteobacteria and is part of the thermotolerant Campylobacter spp., a division within the genus that includes the human pathogen Campylobacter jejuni . The C. lari group is currently composed of five species ( C. lari, Campylobacter insulaenigrae, Campylobacter volucris, Campylobacter subantarcticus, and Campylobacter peloridis ), as well as a group of strains termed the urease-positive thermophilic Campylobacter (UPTC) and other C . lari -like strains. Here we present the complete genome sequences of 11 C. lari group strains, including the five C. lari group species, four UPTC strains, and a lari -like strain isolated in this study. The genome of C. lari subsp. lari strain RM2100 was described previously. Analysis of the C. lari group genomes indicates that this group is highly related at the genome level. Furthermore, these genomes are strongly syntenic with minor rearrangements occurring only in 4 of the 12 genomes studied. The C. lari group can be bifurcated, based on the flagella and flagellar modification genes. Genomic analysis of the UPTC strains indicated that these organisms are variable but highly similar, closely related to but distinct from C. lari . Additionally, the C. lari group contains multiple genes encoding hemagglutination domain proteins, which are either contingency genes or linked to conserved contingency genes. Many of the features identified in strain RM2100, such as major deficiencies in amino acid biosynthesis and energy metabolism, are conserved across all 12 genomes, suggesting that these common features may play a role in the association of the C. lari group with coastal environments and watersheds.